Examining the Benefits and Drawbacks of Retailers using Interactive Technology and Visual Merchadising in Store Environments - Myaesha Ingram; Bridgett Clinton-Scott (Undergraduate Research Journal for the Human Sciences, 2016)
This paper examines how interactive technology has been innovating the retailing industry since the nineteenth century, while improving today through virtual reality and assisted reality. These innovations have had a tremendous impact on visual merchandising displays, both at storefronts and within stores environments, and they affect consumers’ experience (behavior and buying power). The study of immersive technology pushes innovation in the retail process. New tools for improving points of sale have not been widely accepted amongst consumers and retailers and some perceive interactive technologies as enablers and others as disruptors of present retail operations. This research paper will present the benefits and drawbacks of retailers incorporating interactive technologies and innovative visual merchandising strategies into the store environment.
Keywords: Interactive; Technology; Visual; Merchandising